Physical Education in Darul Ulum Islamic Boarding School - Rozi Nasrulloh Akbar; Sugiyanto Sugiyanto; Muchsin Doewes (Kazimierz Wielki University, 2019)
Islamic boarding school (pesantren) is the oldest Islamic educational institutions in Indonesia. Pesantren apply boarding system where student lived and studied theology from the Kyai. pesantren which initially only as Islamic education institutions, today has grown in all aspects, especially in education where schools currently have a formal education that teaches general sciences including physical education. This study will examine the physical education teacher at the boarding school, the subject matter is given in the boarding school and the interest of students in physical education teaching and learning activities. This research is a qualitative descriptive study. Retrieving data using three ways: (1) Observation; (2) Interview and (3) Documents. The results of the research had the following findings: (1) physical education teachers are required to have education diploma instead of pure science. In addition, male teachers must teach male students and female teachers only teach female students; (2) the subject matter provided in pesantren were generally similar to the material provided outside pesantren. It's just giving the material reproduced using the game so that students enthusiastic; (3) the interest of students in physical education teaching and learning activities are very high because the students feel the physical education is a means of removing boredom amid dense boarding activities which lasted from morning till night. The conclusion of this study is the boarding school as Islamic educational institutions currently have a formal education system that teaches general subjects including physical education. Physical education in schools is almost the same as physical education outside schools. It's just that there are some materials that are not taught in schools because it is not in accordance with the teachings of Islam or because they do not have adequate facilities.